2022
DOI: 10.1155/2022/2842278
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of Relevant Factors Affecting the Pregnancy Rate of Frozen-Thawed Embryo Transfer Cycle

Abstract: Objective. The aim of this study is to explore the relevant factors affecting the pregnancy rate of frozen-thawed embryo transfer cycle. Methods. The clinical data of 931 patients who underwent artificial cycle preparation for endometrial FET from April 2017 to November 2020 in the reproductive center of our hospital were retrospectively analyzed. Results. According to the pregnancy situation, the patients were divided into 450 cases of pregnancy and 481 cases of biochemical pregnancy. The univariate analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%